Perineurial Glia Require Notch Signaling during Motor Nerve Development but Not Regeneration - Binari, Laura A. (Society for Neuroscience, 2013)
Motor nerves play the critical role of shunting information out of the CNS to targets in the periphery. Their formation requires the coordinated development of distinct cellular components, including motor axons and the Schwann cells and perineurial glia that ensheath them. During nervous system assembly, these glial cells must migrate long distances and terminally differentiate, ensuring the efficient propagation of action potentials. Although we know quite a bit about the mechanisms that control Schwann cell development during this process, nothing is known about the mechanisms that mediate the migration and differentiation of perineurial glia. Using in vivo imaging in zebrafish, we demonstrate that Notch signaling is required for both perineurial migration and differentiation during nerve formation, but not regeneration. Interestingly, loss of Notch signaling in perineurial cells also causes a failure of Schwann cell differentiation, demonstrating that Schwann cells require perineurial glia for aspects of their own development. These studies describe a novel mechanism that mediates multiple aspects of perineurial development and reveal the critical importance of perineurial glia for Schwann cell maturation and nerve formation.